METHODOLOGICAL GUIDELINES FOR A QUALITY LEARNING - ION ALBULESCU (Studia Universitatis Babes-Bolyai, 2010)
ABSTRACT. The assimilation of information and transforming it in knowledge does not include only a simple taking over, a supply and a later mechanical reproduction. In fact, we are talking about a complex procedure of processing data which is realized in many steps and the individual must make a series of operations. In this study, I tackled the learning as a complex process of mentally processing the information. The result of this process is the fact that the pupil creates notions and opinions, develops understanding, convictions and competences. The identification and the development of those are conditions making the activities more efficient.